Manajemen Kapasitas Jaringan Berbasis Mikrotik Untuk Meningkatkan Kestabilan Internet Di Jaringan Lokal Pada Balai Desa Silo Bonto - Nur Haisyah; Jhonson Efendi Hutagalung; Risnawati (Jurnal Algoritma, 2026)
The main issue with the internet network at the Silo Bonto Village Hall is connection instability caused by a lack of bandwidth management and uncontrolled network usage. This study aims to design and evaluate a MikroTik-based network capacity management system to improve local network performance. The method used was an experiment comparing network conditions before and after the implementation of Simple Queue and Per Connection Queue (PCQ) on MikroTik RouterOS. Testing was conducted using the parameters of throughput, delay, packet loss, and jitter. The results of the study showed an improvement in network performance, marked by an increase in throughput from 8.5 Mbps to 24.6 Mbps, a decrease in delay from 152 ms to 48 ms, a reduction in packet loss from 7.8% to 1.2%, and a decrease in jitter from 38 ms to 9 ms. The main contribution of this research is the application of a combination of the Simple Queue and PCQ methods, which has proven effective in improving stability and bandwidth fairness in networks with limited capacity.